-5(2x-7)-4x=10

Simple and best practice solution for -5(2x-7)-4x=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x-7)-4x=10 equation:



-5(2x-7)-4x=10
We move all terms to the left:
-5(2x-7)-4x-(10)=0
We add all the numbers together, and all the variables
-4x-5(2x-7)-10=0
We multiply parentheses
-4x-10x+35-10=0
We add all the numbers together, and all the variables
-14x+25=0
We move all terms containing x to the left, all other terms to the right
-14x=-25
x=-25/-14
x=1+11/14

See similar equations:

| 83x−1​ =4x+9​ | | -19/2=-23/4x-2x | | 3x+3+5x=3 | | 48=2πr | | -3y=-5+7 | | 9x+10-7x=5(1x+2) | | |4x-2|-6=0 | | 5.8=8.3-0.4x | | -9(y+6)=10(y-2)* | | 7.4x=4.1(2x-4)=-2.3(x-6)-21.6 | | B=8/5(j-99) | | 0=81-0.01s^2 | | x+47-7=23 | | 7(x-2)=4(-8x+1) | | 20k+60k=10k+80 | | −8−3(w+13)=4(w+11)−7w | | 11/7x-5=-341/35+6x-34/5x | | 5c=135 | | 2^x-6/4=10 | | -4=5x-24 | | 4a-20=8a-(4a-20) | | 2x-4=x+8* | | −13(6x-15)=-2x+5 | | (3x+25)+(7x-19)+90=145 | | (k)/(6)=4 | | 7x(3=2x-x)=42=10 | | y/4-2=0 | | -6n+14=-4n-12 | | 2^x-7=9 | | |x+4|+3=1 | | .5x-9=10x+1* | | 8x-38=3x+5 |

Equations solver categories